2017
DOI: 10.1007/s00415-017-8429-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Guillain–Barré syndrome in children and validation of the Brighton criteria

Joyce Roodbol,
Marie-Claire Y. de Wit,
Bianca van den Berg
et al.

Abstract: To describe the key diagnostic features of pediatric Guillain–Barré syndrome (GBS) and validate the Brighton criteria. Retrospective cohort study of all children (<18 years) diagnosed with GBS between 1987 and 2013 at Sophia Children’s Hospital, Erasmus MC, Rotterdam. Clinical information was collected and the sensitivity of the Brighton criteria was calculated. 67 children (35 boys) were included, with a median age of 5.0 years [interquartile range (IQR) 3.0–10.0 years]. Bilateral limb weakness was present at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 15 publications
(22 reference statements)
2
46
2
3
Order By: Relevance
“…Western studies have higher AIDP incidence, whereas axonal variants in most Asian studies [2,4]. In this current study, we also found predominant axonal variants, AMAN being the commonest variant.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Western studies have higher AIDP incidence, whereas axonal variants in most Asian studies [2,4]. In this current study, we also found predominant axonal variants, AMAN being the commonest variant.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that AIDP is reported as the most common variant in western countries, while in Asian countries like Japan, China and India, it comprises only 20-40% [2,4]. Axonal variants were found to be clinically more severe than demyelinating variants in most of the studies [5,6].…”
Section: Introductionmentioning
confidence: 88%
“…There have been several studies reporting on the sensitivity of the Brighton criteria in their GBS patient population (Table 4). 10‐15,21 The sensitivities range from 9% to 91% in different cohorts. In the current study, a level 1 diagnostic certainty was achieved in 67% of patients who had the full complement of clinical and investigation findings.…”
Section: Discussionmentioning
confidence: 99%
“…The case definitions were based on key diagnostic characteristics, CSF examination and NCS 9 . The Brighton criteria has since been widely used by clinicians and has been validated in GBS patients from India, The Netherlands, Korea, Bangladesh, and China with sensitivities for the highest diagnostic certainty ranging from 9% to 91% 10‐15 . However, to date, no study has validated the Brighton criteria in MFS patients.…”
Section: Introductionmentioning
confidence: 99%
“…GBS'nin tanısında 1990 yılında tanımlanan, klinik ve laboratuvar bulguları temel alan Asbury tanı ölçütleriyle birlikte 2009 yılında tanımlanan Brighton tanı ölçütleri de mevcuttur. 10 Tanısal olarak klinik bulgular ön planda olmakla birlikte BOS bulguları ve EMG sonuçları da önem taşımaktadır. Düşük BOS hücre sayısı (≤10 hücre/mm 3 ) ile birlikte yüksek BOS proteini albüminositolojik dissosiasyon olarak adlandırılır ve GBS için tipik sayılan bulgulardandır.…”
Section: Discussionunclassified